Adolescents and self-destructive behaviours: an exploratory analysis of family and individual correlates - Cruz, Diana (2016)
Several studies have shown that as many as 20% of European schooled adolescents report self-destructive thoughts/behaviours. Using multinomial logistic regression analysis, the present study investigated the family and individual variables that predict reports of these behaviours. Three groups, one without reports of self-destructive thoughts/behaviours (NSDTB; n= 998), one with reports of self-destructive thoughts/behaviours (SDTB; n= 268) and a clinical group (CS; n= 42) of adolescents with a mean age of 15.88 (SD= 2.11), participated in the study. Parenting styles, parental attachment, family functioning, satisfaction with family relationships, self-esteem and internalising and externalising symptoms, were analyzed. The findings suggest that increases in mothers’ quality of emotional bond, fathers’ control and family cohesion and decreases in age and mothers’ control lead to a decreased likelihood of belonging to the SDTB group. However, being female, perceiving a high level of mothers’ inhibition of exploration and individuality, perceiving a high level of fathers’ rejection and having a low satisfaction with family relationships increase the probability of belonging to the CS group.